Loss of NOD2 in macrophages improves colitis and tumorigenesis in a lysozyme-dependent manner - Chauvin, Camille; Radulovic, Katarina; Boulard, Olivier; Delacre, Myriam; Waldschmitt, Nadine; Régnier, Paul; Legris, Gauthier; Bouchez, Clément; Sleimi, Mohamed-Yassine; Rosenstiel, Philip; Darrasse-Jèze, Guillaume; Chamaillard, Mathias; et al. (Frontiers in Immunology, 2023)
Abstract Background: Crohn’s disease (CD) is a complex and poorly understood myeloid-mediated disorder. Genetic variants with loss of function in the NOD2 gene confer an increased susceptibility to ileal CD. While Nod2 in myeloid cells may confer protection against T-cell mediated ileopathy, it remains unclear whether it may promote resolution of the inflamed colon. In this study, we evaluated the function of Nod2 in myeloid cells in a model of acute colitis and colitis-associated colon cancer. (CAC). Methods: To ablate Nod2 specifically within the myeloid compartment, we generated LysMCre/+;Nod2fl/fl mice. The role of NOD2 was studied in a setting of Dextran Sodium Sulfate (DSS)-induced colitis and in azoxymethane (AOM)/DSS model. Clinical parameters were quantified by colonoscopy, histological, flow cytometry, and qRT-PCR analysis. Results: Upon DSS colitis model, LysMCre/+;Nod2fl/fl mice lost less weight than control littermates and had less severe damage to the colonic epithelium. In the AOM/DSS model, endoscopic monitoring of tumor progression revealed a lowered number of adenomas within the colon of LysMCre/+;Nod2fl/fl mice, associated with less expression of Tgfb. Mechanistically, lysozyme M was required for the improved disease severity in mice with a defect of NOD2 in myeloid cells. Conclusions: Our results indicate that loss of Nod2 signaling in myeloid cells aids in the tissue repair of the inflamed large intestine through lysozyme secretion by myeloid cells. These results may pave the way to design new therapeutics to limit the inflammatory and tumorigenic functions of NOD2.